Cloning of telomere-associated DNA using single-specific-primer polymerase chain reaction provides evidence for a conserved sequence directly adjacent to Theileria parva telomeric repeats - Sohanpal, B.K.; Bishop, Richard P.; Wasawo, D. (Elsevier, 2000)
Telomere-associated (TA) DNA sequences of the intracellular protozoan parasite Theileria parva were isolated by a novel strategy using a modified version of single-specific-primer polymerase chain reaction (SSP-PCR). Nucleotide sequences of non-coding TA DNA from three telomeres (6017 bp, 2435 bp and 4859 bp) contained no extensive tracts of repetitive DNA. Long open reading frames (ORFs) were present at the centromeric ends of two of the TA sequences, the 3' ends of the closest ORFs being only 2670 bp and 2719 bp from the telomeric repeats. There were regions of significant similarity between the nucleotide sequences of the non-coding regions of different telomeres. The longest region of similarity was a virtually identical 1650 bp domain, located directly adjacent to the telomeric repeats of two separate telomeres. Comparison of the telomere proximal sequences defined in this study and two additional T. parva telomeres, whose sequences were determined previously, resulted in identification of a single copy 141 bp conserved sequence directly adjacent to the telomeric repeats. The conserved sequence is present at all five T. parva telomeres that have been characterized. The only organism currently known to have single copy conserved sequence located adjacent to the telomeric repeats is another intracellular protozoan.